International cooperation in ecological sphere as a factor of life enhancement in the Arctic - Smorchkova, Vera I.; Titovskiy, Aleksey (RUS, 2024)
The article addresses the issue of international cooperation in the northern regions which serves the aim of improving the standard of living among indigenous peoples of the Arctic. The authors give a short history of development of such cooperation. They illustrate international cooperation in the Arctic describing the Russian-Canadian project NORDEP.